2021
DOI: 10.1101/2021.10.29.21265555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IFI27 transcription is an early predictor for COVID-19 outcomes; a multi-cohort observational study

Abstract: BackgroundRobust biomarkers that predict disease outcomes amongst COVID-19 patients are necessary for both patient triage and resource prioritisation. Numerous candidate biomarkers have been proposed for COVID-19. However, at present, there is no consensus on the best diagnostic approach to predict outcomes in infected patients. Moreover, it is not clear whether such tools would apply to other potentially pandemic pathogens and therefore of use as stockpile for future pandemic preparedness.MethodsWe conducted … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Analysis of the dataset using the Boruta feature selection method resulted in the genes IFI27, TPT1, FAM83A, SCGB3A1, TBCE, DCUN1D3, PCSK5, PDGFRB, METRNL, MTRNR2LI2, LGR6, PCDHBD9, DUSP6, SIX5, and RTN2 as biomarker candidate genes for COVID-19. Shojaei et al (26) found that IFI27 transcription was an early predictor for COVID-19 outcomes. They reported that IFI27 was expressed in the respiratory tract of COVID-19 patients and that high IFI27 expression was associated with the presence of a high viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the dataset using the Boruta feature selection method resulted in the genes IFI27, TPT1, FAM83A, SCGB3A1, TBCE, DCUN1D3, PCSK5, PDGFRB, METRNL, MTRNR2LI2, LGR6, PCDHBD9, DUSP6, SIX5, and RTN2 as biomarker candidate genes for COVID-19. Shojaei et al (26) found that IFI27 transcription was an early predictor for COVID-19 outcomes. They reported that IFI27 was expressed in the respiratory tract of COVID-19 patients and that high IFI27 expression was associated with the presence of a high viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the novel biomarker IFI27, it is known to reflect active influenza virus infection, as it appears to be co-expressed with many genes with anti-viral functions and its TLR7-driven expression is observed in DCs and NK cells [ 93 ]. In contrast to the above, others report that there is no difference in the expression of IFI27 and IFITM3 between severe and mild samples [ 38 ] and a study that is currently under peer review supports that the alterations in gene expression reflect only local activity of IFI27 in the lower respiratory tract, as in the lung tissue of deceased individuals suffering COVID-19, IFI27 was upregulated and the overexpression is correlated with high viral load [ 94 ]. On the other hand, a significant association between IFI27 levels in the upper respiratory tract (nasopharyngeal IFI27) and the severity of the disease was reported [ 94 ].…”
Section: Association Of Alterations Of Transcriptomic Signatures In C...mentioning
confidence: 99%
“…In contrast to the above, others report that there is no difference in the expression of IFI27 and IFITM3 between severe and mild samples [ 38 ] and a study that is currently under peer review supports that the alterations in gene expression reflect only local activity of IFI27 in the lower respiratory tract, as in the lung tissue of deceased individuals suffering COVID-19, IFI27 was upregulated and the overexpression is correlated with high viral load [ 94 ]. On the other hand, a significant association between IFI27 levels in the upper respiratory tract (nasopharyngeal IFI27) and the severity of the disease was reported [ 94 ]. This IFN-I related gene is strongly upregulated in COVID-19 patients too and in fact is more elevated in those with severe disease, compared to the mid- and moderate ones, whereas its levels are far lower in critical patients [ 69 ].…”
Section: Association Of Alterations Of Transcriptomic Signatures In C...mentioning
confidence: 99%
“…Moreover, in another multi-cohort observational study, IFI27 was shown to be expressed in COVID-19 infected patients, and its level of expression was associated with the presence of a high viral load (36). These results are promising although further validation is required to achieve high specificity of this gene marker to a particular disease.…”
Section: Influenza and Respiratory Syncytial Virusmentioning
confidence: 91%